(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aimed to calculate the economic return of adopting the integrated pest management – IPM program for pests that affect palm trees from the economic perspective, by measuring the impact of its application on some economic variables (total costs, average production, and net profit) per donum which is a quarter of a hectare. The results showed that the application of IPM positively impacts the average production, as it reached the levels of application (low, medium, and high) of about (1647, 2161.3, and 1798.5) dinars/ donum respectively. As well as the positive impact in reducing costs, the results showed that the costs for the same application levels amounted to (177897, 171362, and 122109) dinars/ donum respectively. Also, the net profit has been positively affected by the program on farmers who apply the program in a medium and high manner compared to those who apply it low. The results showed that the net profit amounted to (61945, 97104, and 100599) dinars/ donum respectively. The research recommended increasing support for programs using modern control methods in control to reduce costs and protect the environment, as well as increasing financial support for the integrated pest management program in Karbala Governorate and extension programs in the field of eco-friendly control.